(untitled) (Comprehensive Journal of Science, 2026)
This study presents the design and construction of a physicochemical treatment tower for groundwater purification in the Al-Ajilat region. The treatment system utilized olive cake (olive pomace), a by-product of Libyan olive oil extraction, as a filtration medium with varying thicknesses (1.5–5 cm). Experimental evaluation through chemical and biological analyses confirmed significant improvements in water quality and biological safety. The system effectively reduced turbidity, calcium carbonate, chlorides, and concentrations of calcium and potassium ions. In addition, the olive-based filtration layer demonstrated efficiency in decreasing sodium ion levels, suggesting its potential integration with reverse osmosis membrane materials. The results revealed a non-linear relationship between filtration layer thickness and contaminant removal efficiency, attributed to magnesium accumulation on the filter medium, which influenced ion-exchange behavior. The findings demonstrate the viability of olive pomace as an effective and sustainable material for groundwater treatment and support its potential application in waste recycling and environmental management.